Statistical Analsysis to Evaluate Heavy Metal Pollution in the Air Obatained by Moss Technique in Hanoi and its Surrounding Region - Quyet, N. H.; Khiem, Le Hong; Quan, V. D.; My, T. T. T.; Frontasieva, M. V.; My, N. T. B.; Nam, L. D.; Mai, N. N.; Hong, K. T.; Tien, D. P. T.; Thang, D. V.; Trung, T. D.; et al. (Communications in Physics, 2019)
The aim of this paper was the application of statistical analysis including principal component analysis to evaluate heavy metal pollution obtained by moss technique in the air of Ha Noi and its surrounding areas and to evaluate potential pollution sources. The concentrations of 33 heavy metal elements in 27 samples of Barbula Indica moss in the investigated region collected in December of 2016 in the investigated area have been examined using multivariate statistical analysis. Five factors explaining 80% of the total variance were identified and their potential sources have been discussed.